Estrutura populacional, uso de ambientes e crescimento corporal de Rhinoclemmys punctularia punctularia (DAUDIN, 1801), na Ilha de Algodoal/Maiandeua, Maracanã, Pará, Brasil - FIGUEIREDO, Manoela Wariss (Universidade Federal do Pará, 2013)
For Rhinoclemmys punctularia punctularia (Daudin, 1801), until this study, there were no further studies that focused on their ecology in natural environment. In general, the existing works are based on few records at different locations in range of the species and data from animals in captivity, such reports have described the species as a generalist in relation to their feeding and the use of environments. This study aimed to evaluate the use of environments, the population structure and estimate the constant growth of the Rhinoclemmys punctularia punctularia in Island of Algodoal/Maiandeua, which is an environmental protection area (APA). As methodology were conducted experimental fishing in different environments of the APA of Algodoal/Maiandeua, between the years 2008 and 2009. Of the sampled specimens were captured only environments without the influence of marine waters and abundant food resources, such as the fruits of Annona sp. and Chysobalanus sp.. Environments used by R. p. punctularia (flooded forest, temporary ponds and lagoons of the plain), the highest yields were found in lagoons of the plain, where there is a greater availability of fruits of Annona sp. and Chysobalanus sp in water bodies that the species occupies. The population of R. p. punctularia in Algodoal/Maiandeua is mainly composed of adults and is slightly skewed towards females (0.43 males). The average length of females is 195.42±18 mm (range 43-226 mm) (n=68) while the males is 167±12.7 mm (range 133-197mm) (n=64), the females being statistically larger than males (U=454.02; GL=132, p=0.0001, n=132). In both sexes there was a significantly negative relationship between growth rate and length of the carapace. The model of von Bertallanfy was an estimated value of k=0.19 year-1 for males and k=0.16 year-1 for females, since the values of L∞ were 207.36 mm and 237.89 mm for males and females, respectively. When you reach the CRC 237 mm for females and 207 mm for males, the species reaches the age of about 33 years in both sexes.